2021
DOI: 10.3389/fonc.2020.620641
|View full text |Cite
|
Sign up to set email alerts
|

Metformin: Targeting the Metabolo-Epigenetic Link in Cancer Biology

Abstract: Metabolism can directly drive or indirectly enable an aberrant chromatin state of cancer cells. The physiological and molecular principles of the metabolic link to epigenetics provide a basis for pharmacological modulation with the anti-diabetic biguanide metformin. Here, we briefly review how metabolite-derived chromatin modifications and the metabolo-epigenetic machinery itself are both amenable to modification by metformin in a local and a systemic manner. First, we consider the capacity of metformin to tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 92 publications
0
6
0
Order By: Relevance
“…Recent studies suggested that maternal and paternal exercise may affect the metabolic health in adult offspring (Zheng et al, 2020) and sperm epigenome can be epigenetically modified by environmental factors and the health of the offspring can be affected by the transgenerational passage of the modified epigenome (Xu et al, 2021). Metformin may regulate epigenetic modifications (Menendez, 2020) and these have been considered as one of the mechanisms explaining the beneficial effects of metformin on the prevention of cancer (Cuyàs et al, 2021) and aging (Menendez, 2020). Some recent studies suggested that in utero exposure to metformin may reduce fertility in male offspring in adulthood (Faure et al, 2021) and that maternal exposure to metformin may induce epigenetic modifications via placental mitochondrial biogenesis (Jiang et al, 2020).…”
Section: Metformin May Adversely Affect Sexual Functionsmentioning
confidence: 99%
“…Recent studies suggested that maternal and paternal exercise may affect the metabolic health in adult offspring (Zheng et al, 2020) and sperm epigenome can be epigenetically modified by environmental factors and the health of the offspring can be affected by the transgenerational passage of the modified epigenome (Xu et al, 2021). Metformin may regulate epigenetic modifications (Menendez, 2020) and these have been considered as one of the mechanisms explaining the beneficial effects of metformin on the prevention of cancer (Cuyàs et al, 2021) and aging (Menendez, 2020). Some recent studies suggested that in utero exposure to metformin may reduce fertility in male offspring in adulthood (Faure et al, 2021) and that maternal exposure to metformin may induce epigenetic modifications via placental mitochondrial biogenesis (Jiang et al, 2020).…”
Section: Metformin May Adversely Affect Sexual Functionsmentioning
confidence: 99%
“…Controlling how nucleosome structure and function are regulated, for example, promoting chromatin relaxation, increasing histone acetylation by inhibiting HDACs, decreasing histone methylation, increasing histone ribosylation, and inhibiting histone O-GlcNAcylation are crucial. [56,57] Activating neural precursor cells is a potential approach to treating brain damage. Ruddy et al showed that metformin activates neural precursor cells, promotes differentiation of cells and leads to functional motor recovery in a neonatal stroke model, depending on age and gender.…”
Section: Resultsmentioning
confidence: 99%
“…Metformin has the ability to alter these pools. [ 56 ] Metformin inhibits mitochondrial complex I and oxidative phosphorylation, thus increasing the AMP:ATP ratio, thereby activating AMPK. Histones and histone‐modifying enzymes are phosphorylated as a result of AMPK activation.…”
Section: Discussionmentioning
confidence: 99%
“…31 Metformin induces autophagy, causes cell cycle arrest and is also associated with the metabolo-epigenetic link in cancer. 78,79 So for all these reasons, we have chosen a m-TOR blocker metformin in combination with siRNA mediated Notch1 silencing.…”
Section: Designing Combination Therapy and Evaluation Of Its Effect O...mentioning
confidence: 99%